PRODUK-PRODUK UNGGULAN BANK SYARIAH YANG DIMINATI KAUM PEREMPUAN - Rahim, Abdul (An - Nisa`, 2011)
Housing finance (mortgage) is one of the flagship products held by the Bank Syariah Mandiri, therefore this product is very much demand, especially the woman. Based the analysis of the author that the fundamental reason for woman with high demand in housing financingin particular is one of alternatif for the future of their families. So almost all of Bank Syariah Mandiri in Indonesia in general thet the housing or mortgage a higher demand for woman.Besides another product of interest is womanâs car buying either new or used. On the other hand that the financing for this car is not much time with housing finance.